Etika Profesi Guru: Fondasi Kinerja dan Kredibilitas dalam Perspektif Literatur - Badri, Syahriwal; Khairat, Annisaul (Jurnal Manajemen Pendidikan Islam (MANAPI), 2025)
Professional ethics in teaching play a crucial role in shaping the quality of education; however, its implementation in practice still faces numerous challenges, such as inconsistent application of ethical values and the lack of continuous ethics training. This study aims to analyze the influence of professional ethics on teachers’ performance and credibility through a qualitative descriptive approach using a literature review method. Data were obtained from scholarly literature published between 2020 and 2025, including accredited journals and relevant academic books. Data were collected using a manual literature data recording format and analyzed through content analysis and thematic analysis techniques. The findings reveal that understanding and applying ethical values such as integrity, responsibility, and fairness significantly enhance teachers' dedication and performance in the teaching process. Moreover, professional ethics also reinforce teachers’ credibility in the eyes of students, colleagues, and the community by increasing trust and appreciation for the teaching profession. In conclusion, professional ethics not only support teachers’ technical performance but also serve as a moral foundation that strengthens their professional identity and social position as role models. Therefore, strengthening professional ethics should be a key priority in teacher development and performance evaluation efforts.